2019
DOI: 10.1101/838847
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A/T/N polygenic risk score for cognitive decline in old age

Abstract: Research in Context Systematic ReviewAuthors reviewed relevant literature using PubMed and Google Scholar. Key studies that generated and validated polygenic risk scores (PRS) for clinical and pathologic AD were cited. PRS scores have been increasingly used in the literature but clinical utility continues to be questioned. InterpretationIn the current research landscape concerning PRS clinical utility in the AD space, there is room for model improvement and our hypothesis was that a PRS with integrated risk fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…Previous studies have replicated the association of variants used for PRS construction and validated the relationship of the GWAS with CSF amyloid levels in independent cohorts, providing strong evidence for their true association. 18,51 Our study corroborates the ability of PRS for amyloid to predict AD/aMCI risk in a genetically different group than previous studies' population.…”
Section: Incident Ad or Amci (%) Hr (95% Ci) Psupporting
confidence: 87%
See 3 more Smart Citations
“…Previous studies have replicated the association of variants used for PRS construction and validated the relationship of the GWAS with CSF amyloid levels in independent cohorts, providing strong evidence for their true association. 18,51 Our study corroborates the ability of PRS for amyloid to predict AD/aMCI risk in a genetically different group than previous studies' population.…”
Section: Incident Ad or Amci (%) Hr (95% Ci) Psupporting
confidence: 87%
“…This is in accordance with previous studies that used summary statistics from the GWAS of Deming et al 28 to derive a PRS for amyloid. 18,51 The PRS was constructed excluding the APOE region, suggesting that genetic variation beyond APOE accounts for a substantial proportion of AD/aMCI genetic risk. Indeed, the addition of PRS in the adjusted model with APOE as main predictor increased the proportion of variance explained by 1.1%.…”
Section: Incident Ad or Amci (%) Hr (95% Ci) Pmentioning
confidence: 99%
See 2 more Smart Citations
“…AD-PRS also showed a significant correlation with the A/T/N profiles (Ebenau et al, 2021 ). A study found that the integration of genetic risk across the AD biomarkers like A/T/N may improve the prediction of the disease progression (Moore et al, 2019 ).…”
Section: Associations Of Ad-prs With Cerebrospinal Fluid and Plasma B...mentioning
confidence: 99%